Faculty development : achieving change through action research - Ewell, B. Sara; Giblin, Joan; McNabb, Joe (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"Action Research can empower all administrators in higher education to engage more effectively in resolving challenges in colleges and universities. Scholar-practitioners are particularly well poised to impact three defined areas of practice: college students, faculty, and curriculum, teaching and learning. Through these three areas of foci broad issues within higher education are explored. Action Research is a powerful, localized methodology for impacting difficult and complex issues embedded in organizations. Higher education administrators regularly confront these types of difficult issues and hold the responsibility to solve these problems"-- Provided by publisher.
Keywords: College teachers -- In-service training.; Universities and colleges -- Faculty.; Action research in education.; Universities and colleges -- Administration.; Education -- Professional Development.; Teacher training.; elektronické knihy; electronic books